Vehicle Dynamic Simulation Possibilities Using AVL Cruise M - Nemes, Dániel; Pálfi, Tibor; Hajdu, Sándor (International Journal of Engineering and Management Sciences, 2020)
In most cases, when creating vehicle dynamics simulations, we need software that can speed up model creation and simulation. There are many programs on the market for this purpose, but they have different knowledge and user interfaces. We present in this article briefly introduces the use of one of the market’s leading vehicle simulation software, the AVL Cruise M.